Suplementasi Urea Molasis Blok untuk Meningkatkan Penampilan Kambing Peranakan Etawah yang Diberi Pakan Hijauan Gamal - Ni Wayan Siti; I. G. M. A. Sucipta; I. M. Mudita; I. B. G. Partama; I.G.L.O. Cakra (Agricultural Faculty, 2012)
The supplementation of urea molasses block for increasing performance of ettawah crossbred goats fed diet containing gliricidia spium green forage ABSTRACT. The aimed of this experiment to study the supplementation of urea molasses block for performance increased of ettawah crossbred goats fed diet containing Gliricidia spium green forage has been conducted at Tabanan regency and Animal Nutrition Laboratory. The Latin Square Design which four treatments and four replicates was used in this experiment. The four treatments were the levels of urea molasses block : 0, 50, 100 and 150g respectively. The animal access to ad libitum Gliricidia spium green forage and drink water. The animal fed twice a day urea molasses block at the morning and at the afternoon. The variables which were observed including feed consumption, nutrient digestibility, body weight gain and feed conversion ratio. The result of this experiment showed dry matter feed consumption, drink water, nutrient digestibility of the four treatments is not significantly different (P 0.05). The body weight gain at treatment C was significantly higher (P 0.05), but feed conversion ratio (FCR) was significantly lower (P 0.05) than treatments A, B and D. From the results in this experiment it can be concluded that the used of urea molasses block 100g on the effect to increased the performance of ettawah crossbred goats with basal diet Gliricidia spium green forage.